Silent Infection of B and CD8 + T Lymphocytes by Influenza A Virus in Children with Tonsillar Hypertrophy - Castro, Italo A; Jorge, Daniel M M; Ferreri, Lucas M; Martins, Ronaldo B; Pontelli, Marjorie C; Jesus, Bruna L S; Cardoso, Ricardo S; Criado, Miria F; Carenzi, Lucas; Valera, Fabiana C P; Tamashiro, Edwin; Anselmo-Lima, Wilma T; et al. (Journal of virology, 2020)
Influenza A viruses (IAVs) cause more than 2 million annual episodes of seasonal acute respiratory infections (ARI) and approximately 500,000 deaths worldwide. Depending on virus strain and host immune status, acute infections by IAV may reach sites other than the respiratory tract. In the present study, IAV RNA and antigens were searched for in tissues of palatine tonsils and adenoids removed from patients without ARI symptoms. A real-time reverse transcriptase PCR (RT-PCR) screening revealed that 8 tissue samples from 7 patients out of 103 were positive for IAV. Positive samples were subjected to next-generation sequencing (NGS) and 3 of 8 tissues yielded complete IAV pH1N1 genomes, whereas in 5 samples, the PB1 gene was not fully assembled. Phylogenetic analysis placed tonsil-derived IAV in clusters clearly segregated from contemporaneous Brazilian viruses. Flow cytometry of dispersed tissue fragments and serial immunohistochemistry of paraffin-embedded sections of naturally infected biopsies indicated that CD20 B lymphocytes, CD8 T lymphocytes, and CD11c cells are susceptible to IAV infection. We sought to investigate whether these lymphoid tissues could be sites of viral replication and sources of viable virus particles. MDCK cells were inoculated with tissue lysates, enabling recovery of one IAV isolate confirmed by immunofluorescence, reverse transcriptase quantitative PCR (RT-qPCR), and NGS. The data indicate that lymphoid tissues not only harbor expression of IAV proteins but also contain infectious virus. Asymptomatic long-term infection raises the possibility of IAV shedding from tonsils, which may have an impact on host-to-host transmission. Influenza A virus (IAV) infections are important threats to human health worldwide. Although extensively studied, some aspects of virus pathogenesis and tissue tropism remain unclear. Here, by different strategies, we describe the asymptomatic infection of human lymphoid organs by IAV in children. Our results indicate that IAV was not only detected and isolated from human tonsils but displayed unique genetic features in comparison with those of contemporaneous IAVs circulating in Brazil and detected in swabs and nasal washes. Inside the tissue microenvironment, immune cells were shown to be carrying IAV antigens, especially B and T CD8 lymphocytes. Taken together, these results suggest that human lymphoid tissues can be sites of silent IAV infections with possible impact on virus shedding to the population.